Intervensi Psikoedukasi untuk Mengurangi Isu Kesehatan Emosional pada Pasien Diabetes - Rohmah, Assyfa Siti; Yulia, Yulia; Yona, Sri; Kurnia, Dikha Ayu (FORIKES, 2025)
Emotional health problems such as depression, distress, anxiety and fear are important points that need to be considered in the management of diabetes patients. Emotional health problems that are not handled properly can interfere with the success of diabetes management and increase the risk of complications. One thing that can be done to reduce emotional health problems is to conduct psychoeducational interventions. Psychoeducational interventions focus on cognitive, behavioral and emotional changes. The purpose of this literature study was to describe psychoeducational interventions that can reduce the severity of emotional health problems in diabetes patients. This literature study was conducted using the PRISMA approach and the quality of the articles was assessed based on the RoB V2 from Cochrane. There were 13 articles in this literature study with RCT and pilot RCT designs. Four articles discussed the effectiveness of psychoeducational interventions using cognitive-behavior therapy, 7 articles used telehealth-based education and 2 articles on mindfulness. Of all the literature reviewed, all showed the success of interventions in order to improve the level of mental health of patients including depression, distress and anxiety, both in the long and short term. Furthermore, it was concluded that psychoeducational interventions are effective in improving mental health in diabetes.Keywords: diabetes; emotional health; depression; distress; anxiety; fear of hypoglycemia ABSTRAK Masalah kesehatan emosional seperti depresi, distres, ansietas dan ketakutan merupakan poin penting yang perlu diperhatikan dalam manajemen pasien diabetes. Masalah kesehatan emosional yang tidak ditangani dengan baik dapat mengganggu keberhasilan manajemen diabetes dan meningkatkan resiko komplikasi. Salah satu hal yang dapat dilakukan dalam mengurangi masalah kesehatan emosional yaitu melakukan intervensi psikoedukasi. Intervensi psikoedukasi berfokus terhadap perubahan kognitif, perilaku dan emosional. Tujuan studi literatur ini yaitu menggambaran intervensi psikoedukasi yang dapat menurunkan keparahan dari masalah kesehatan emosional pada pasien diabetes. Studi literatur ini dilakukan menggunakan pendekatan PRISMA dan kualitas artikel dinilai berdasarkan RoB V2 dari Cochrane. Terdapat 13 artikel pada studi literatur ini dengan desain RCT dan pilot RCT. Empat artikel membahas efektivitas intervensi psikoedukasi menggunakan cognitive-behavior therapy, 7 artikel menggunakan edukasi berbasis telehealth dan 2 artikel mengenai mindfulness. Dari seluruh literatur yang ditinjau, semuanya menunjukkan keberhasilan intervensi dalam rangka meningkatkan level kesehatan mental pasien yang mencakup depresi, distress dan ansietas, baik dalam jangka panjang maupun jangka pendek. Selanjutnya disimpulkan bahwa intervensi psikoedukasi efektif untuk meningkatkan kesehatan mental diabetes. Kata kunci: diabetes; kesehatan emosional; depresi; distress; ansietas; ketakutan akan hipoglikemi